Manajemen risiko kepatuhan syariah dalam praktik perbankan syariah: studi kasus bank muamalat indonesia - Putra Rofiqi, Alif Ahmad Sulthoni (Maliki Interdisciplinary Journal, 2025)
This study examines sharia compliance risk management in sharia banking practices with a case study of Bank Muamalat Indonesia, a pioneer of sharia banking in Indonesia. Using a qualitative approach and literature study, the study identified various sharia compliance risks faced, such as product inconsistencies with DSN-MUI fatwas, errors in contract implementation, and regulatory and technological challenges. The study highlights the importance of the role of the Sharia Supervisory Board (DPS), compliance units, and information technology integration in identifying, monitoring, and controlling these risks. The findings indicate that effective sharia compliance risk management requires a comprehensive approach involving strengthening supervision, HR training, and a real-time digital transaction monitoring system. This study is expected to be a reference for the development of a comprehensive and sustainable sharia risk management system in the sharia banking industry in Indonesia.